plan de marketing para los actractivos turisticos naturales del canton chaguarpamba provincia de loja - Tapia Pacheco., Liliana Elizabeth (2016)
This thesis project titled MARKETING PLAN FOR THE TOURIST ATTRACTIONS Chaguarpamba Canton, Loja province, it aims to promote and disseminate the attractions through the development of a tourism marketing planIt is here in this province where the Chaguarpamba Canton which has an urban parish Chaguarpamba and four rural which way they are right supplemented with communities, this location enjoys a mild climate for agriculture, livestock and tourism, has a variety tourist attractions which are unknown to much of the population. It is for this reason that we have chosen the following thesis topic "Marketing Plan for the development of the tourist attractions of Canton Chaguarpamba province of Loja" To which objectives for the development of this research was defined being marked in a general purpose and three specific objectives: 1. Conduct a situational analysis of the canton tourist Chaguarpamba province of Loja, 2. Perform a marketing proposal to the sites Chaguarpamba Canton province of Loja, and socializing 3. Perform marketing Plan Chaguarpamba Canton province of Loja. Within the methods and techniques applied technique is the survey that 372 surveys, which the residents of Canton Chaguarpamba, which helped us to meet the tourist demand of this place was made were implemented. A diagnosis using SWOT analysis, which allowed us to know the strengths and weaknesses that place, to do the interview technique Canton Mayor Ing was used. Leader Cordova R, as well as observation technique was developed. The results are checked by meeting three specific objectives: making the diagnosis of the current situation of tourism in the canton Chaguarpamba that allowed integrating the components of the tourism system to collect information necessary for the fulfillment of this project, the determination of tourism demonstrating the tourism potential with 4 locations identified these located within the canton Chaguarpamba: Cerro surapo, saraguallas Lagoon, Infiernillos hill, hill Chincha Cross and other attractions at the county level and its gastronomy whose typical dish is Molloco the other aside a minimum number of service providers in the tourism sector was identified; to identify tourism demand in the canton Chaguarpamba surveys were conducted that helped them determine the profile of tourists; determining strengths and weaknesses of the canton Chaguarpamba could be determined through SWOT analysis, and thus be able to identify key objectives and needs strengthening tourism in this area and possible solutions 5 Concluding that tourists visiting the Canton Chaguarpamba know about the attractions found in the canton, but this in turn does not have a plant tour, where people can perform any activities immersed in tourism, the same as after the socialization they showed interest in carrying out the marketing plan and likewise receive training to be ready to receive tourists and provide a service to know; It is recommended to the cantonal authorities Chaguarpamba or person concerned to show this work to the entire population thus achieving a union between neighborhoods and communities to strengthen the organization, in the same way that the authorities seek support office ITUR for the charge conduct a study on the training they should receive the inhabitants of the county. Later necessary appropriate recommendations are set to improve tourism in the county among the most important is to promote awareness of the people to achieve the valuation of natural and cultural resources it possesses, which will lead to economic development and tourism not only in the study site but nationally.